2006
DOI: 10.1016/j.chroma.2005.10.052
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the herbicide metribuzin and its major conversion products in soil by micellar electrokinetic chromatography

Abstract: In this paper, a multiresidue method for the analysis in soils of metribuzin (M) and its major conversion products, deaminometribuzin (DA), diketometribuzin (DK) and deaminodiketometribuzin (DADK) is developed. Considering the neutral and charged nature of the molecules, micellar electrokinetic chromatography (MEKC) is a very efficient method for the separation of these compounds, providing high efficiency and short analysis times. Different electrophoretic parameters were studied to optimize the separation, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…This method was successfully applied to the soil samples without a preliminary clean-up procedure, and the herbicides were measured without any interference from coexisting substances. Another study by Huertas-Perez et al [91] reported the use of MEKC for the analysis of metribuzin and its major conversion products in soils. Soil samples were extracted in an ultrasonic bath using methanol and an SPE procedure was then applied to cleanup and concentrate the analytes using a LiChrolut EN sorbent column.…”
Section: Pesticides and Herbicidesmentioning
confidence: 98%
See 1 more Smart Citation
“…This method was successfully applied to the soil samples without a preliminary clean-up procedure, and the herbicides were measured without any interference from coexisting substances. Another study by Huertas-Perez et al [91] reported the use of MEKC for the analysis of metribuzin and its major conversion products in soils. Soil samples were extracted in an ultrasonic bath using methanol and an SPE procedure was then applied to cleanup and concentrate the analytes using a LiChrolut EN sorbent column.…”
Section: Pesticides and Herbicidesmentioning
confidence: 98%
“…Various approaches, including the improvement of detection system capabilities and/or preconcentration techniques, as outlined in Sections 2 and 3, have been proposed. This has resulted in the development of CE as an advantageous analytical tool that provides the separation power and detectability necessary for the analysis of trace amounts of pesticides [27,33,41] and herbicides [31,32,50,51,64,[89][90][91] in different environmental matrices.…”
Section: Pesticides and Herbicidesmentioning
confidence: 99%
“…It is an attractive and simple analytical technique with a high efficiency, rapid separation speed of analysis, small consuming sample and low consumption of sample reagents (Hernández-Borges, Frías-García, Cifuentes, & Rodríguez-Delgado, 2004;Hernández-Borges, Rodríguez-Delgado, García-Montelogo, & Cifuentes, 2004;Hernán-dez-Borges, Rodríguez-Delgado, García-Montelogo, & Cifuentes, 2005a, 2005bHuertas-Pérez, del Olmo Iruela, García-Campaña, González-Casado, & Sánchez-Navarro, 2006;Pérez-ruíz, Martínez-Lozano, Sanz, & Bravo, 2005;Ravelo-Pérez, Hernández-Borges, & Rodríguez-Delgado, 2006;Zawiyah et al, 2007). CE has become a very useful tool for organic contaminants compounds but CE coupled to UV-detector, present a scarcely sensitive.…”
Section: Introductionmentioning
confidence: 97%
“…Analysis of metribuzin has mainly been accomplished by different chromatographic methods such as liquid chromatography [5][6][7], micellar electrokinetic chromatography [8], solid-phase extraction and sample stacking-micellar electrokinetic capillary chromatography [9], capillary gas chromatography [10], capillary zone electrophoresis [11] and molecularly imprinted polymer [12]. All these methods are expensive, require long separation times and sometimes need the development of extremely complex gradient for the separation.…”
Section: Introductionmentioning
confidence: 99%